Intermittent Hypoxia Interferes with Autocrine Effects of GABA on Insulin Secretion in Postnatal Rodents-Implications for Pediatric Obstructive Sleep Apnea - Eung-Kwon Pae; Man-Kyo Chung; Ronald M. Harper (MDPI AG, 2022)
Gamma-amino butyric acid (GABA) is well known to help elevate pancreatic β cell vitality and insulin levels in blood. GABA works via a coupling with GABA receptors; thus, the concentration of GABAA receptors on the plasma membrane of β cells appears to be critical for insulin regulation. Various medical conditions, such as pediatric and adult obstructive sleep apnea (OSA), show high levels of Type 2 diabetes; such patients also are exposed to intermittent hypoxia (IH), which modifies the GABA levels. To evaluate the potential therapeutic roles of GABA for diabetic patients with OSA, we studied the interactions of IH with GABA and GABAA receptors in young rats. Using rat pups and primary pancreatic islets, we evaluated the roles of GABA in insulin secretion. We show that GABA effectively increased the insulin secretion of pancreatic islets under normal ambient oxygen levels, as well as in culture medium with a glucose level of 2 mM. GABA also increased islet insulin secretion conditioned under IH in a 16 mM glucose medium. When islets were IH-treated, insulin secretion decreased due to lower intracellular chloride levels in accordance with the increased KCC2 levels. The results show that IH challenges down-regulate the GABAA receptor levels in pancreatic islets, which decreases GABA-GABAA receptor coupling action, as well as membrane depolarization for insulin secretion. The findings have the potential to suggest novel interventions for insulin regulation during IH of disordered breathing, including OSA.